The IMPLEMENTATION OF THE TECHNIQUE OF ROTOSCOPING IN THE SHORT FILM GENRE THRILLER USING METHOD VILLAMIL-MOLINA - Muhammad Adam Firdaus AZ; Muchamad Fajri Amirul Nasrullah (Politeknik Negeri Batam, 2019)
The development of the film industry is currently growing rapidly, it does have animpact on existing technologies especially in editing techniques, thereby causing thenumber of genres that are popping up, and one was a thriller. This can occur becausethe editing techniques facilitate the videographer to create a fictitious scenes becomelook real. Rotoscoping is one frequently used editing techniques to create it.Rotoscoping itself is a technique in film editing by means of tracing live action videofootage frame by frame with filter picture selectively from each section that is in theframe and give a more realistic impression in a film. In this final task, later made afilm genre thriller, which applies the technique of rotoscoping in Adobe After Effects.The film stresses on the side of his editing, and is expected to later can add insightinto the young film makers in the world of cinema.